A Neurotic Extrovert Who is Open to New Experiences? Understanding How Personality Traits May Impact the Commenting Behaviors of Online News Readers. Issue 3 (3rd July 2017) - Barnes, Renee; Mahar, Dough; Wong, Ides; Rune, Karina
Abstract : This article develops a theoretical context for the influence of personality traits on commenting behaviors on online news Web sites. Drawing on the literature of personality, and online behaviors, we examine how personality traits may influence which individuals make contributions on news Web sites. Additionally the article focuses on how the commenting "landscape, " in particular moderation policies and user interfaces, may impact those who contribute.